THE EVALUATION OF GOOD MANUFACTURING PRACTICES (GMP) IN FISH PROCESSING SME CENTER CASE STUDY OF BALIKPAPAN CITY - Taufik Hidayat; Zulfatun Najah; Nia Ariani Putri; Zulmaneri Zulmaneri (University of Sultan Ageng Tirtayasa, 2019)
The application of Good Manufacturing Practices (GMP) is a parameter towards Hazard Analytical Critical Control Procces (HACCP). The Center for Small and Medium Enterprise (SME) X in Balikpapan needs to evaluate its production process to improve the fisheries processing industry that fits the GMP criteria. This study aims to evaluate the application of GMP in fish processing SEM Center. GMP evaluation carries out by looking at the production and building processes through interview and documentation. The evaluation result shows that the facilities and infrastructure of SEM center need to be improved to meet the implementation of good GMP, since it has many critical and major deviations that need to be enhanced in terms of buildings and production processes. Based on the observations, it shows that there are 20 minor findings, 30 major findings, 28 serious findings, and 30 critical findings that are found. Deviations in the SEM center is categorized as D grade, so they are not feasible for a production process.